CLUSTERING OF TERRITORIAL AREAS: A MULTI-CRITERIA DISTRICTING PROBLEM - Fragoso, Rui (2014)
Endogenous resources, economic profile and socio-economic issues are the criteria that define the development level and the identity features of a territorial unit. The territorial units that organize the country, in political and administrative terms – parishes and counties –, have a hierarquical structure, which initially reflected the organization of productive activities as well as the tradition State organization. The success of development policies addressed to territorial agglomerates depends on its homogeneity and of their territorial units. Facing to this the clustering of territorial areas can be stated as a districting multi-criteria problem. Thus, this paper aims to propose a framework for obtaining homogenous territorial clusters based on a Pareto frontier that includes multicriteria related to the territorial endogenous resources, economic profile and sociocultural features. This framework is developed in two phases. First, the criteria correlated with the development at the territory unit level are determined through statistical and econometric methods. Then, a multi-criteria approach is developed to allocate each territory unit to an agglomerate of territory according to the Pareto frontier established. The framework is applied to the context of a set of parishes and counties of the Alentejo Central region, southern Portugal. Results are presented and discussed in the scope of a regional strategy of development.